Party Institutional Perspectives on Open Proportional System Flaws - Widiono, Alfonsus Ryan; Zhang, Sheng (CV. Era Digital Nusantara, 2024)
Abstract: Concerns emerge from the potential implementation of an open proportional system, where parliamentary candidates may wield more influence than the political parties endorsing them. This situation undoubtedly poses a risk of undermining the institutional strength of political parties. Purpose: The primary objective of this paper is to examine and compare the implementation of general elections, focusing on the election mechanisms employed in both open and closed proportional systems. Design/Methodology/Approach: The methodology employed in this paper is a legal research method, specifically the normative legal research type. The approach adopted includes both a statute approach and a conceptual approach. The legal materials utilized encompass primary and secondary legal sources. Findings: The study findings indicate that the use of general elections with an open proportional system is incongruent with the mission and vision of political parties. In this system, the priority is often placed on candidates' popularity rather than their adherence to party ideology, political experience, and organizational skills. Consequently, candidates exert a disproportionate influence on the party's direction, diminishing the party's role as a robust institution. Therefore, the reinstatement of a closed proportional system in Indonesia is deemed essential. This system ensures that elected candidates align with the party's ideology, reinforcing the party's institutional strength. In advocating for a closed proportional system, the study underscores its cost-effectiveness. This system minimizes the likelihood of candidates engaging in fraudulent activities, as financial incentives to election organizers are reduced. Furthermore, the study emphasizes the importance of voters being well-informed about a political party's proposed path of progress to make informed decisions during elections. Originality/value: There has been no prior research examining the open proportional system from the perspective of political party institutions. This study is considered pioneering as researchers advocate for the adoption of a closed proportional system to fortify political party institutions, emphasizing the perceived degradation of these institutions. The argument presented suggests that the strength of political parties has diminished, with individual candidates wielding more influence. In contrast to the prevailing trend, the researchers endorse a closed proportional system, positing that the strength of political parties should be the determining factor rather than relying on the strength of individual candidates.